Peran Guru Agama Katolik dalam Menanamkan Semangat Multikultural Melalui Pendidikan Agama Katolik - Lidwina Prada L; Nikolaus Anggal; Komela Avan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to describe the role of Catholic religion teachers in instilling a multicultural spirit through Catholic Religious Education at SMP Katolik 2 W.R. Soepratman Barong Tongkok. The research was motivated by the urgent need to promote multicultural awareness in Catholic schools, especially in response to persistent issues of discrimination and exclusion among students. These challenges highlight the importance of Catholic religion teachers as character builders who foster inclusive and peaceful coexistence within a diverse school community. The research employed a descriptive qualitative approach using method triangulation. Data were collected through in-depth interviews with teachers and the principal, classroom observations, document analysis, and online questionnaires to students as supplementary data. Data analysis followed the Miles and Huberman model, involving data reduction, display, and conclusion drawing. The findings reveal that Catholic religion teachers go beyond teaching doctrinal content; they also act as educators, facilitators, mentors, and promoters of multicultural values. These roles are manifested in learning strategies such as Biblical reflections, group discussions, drama projects, and anti-discrimination classroom agreements. This study emphasizes that Catholic Religious Education plays a vital role in shaping students’ awareness and attitudes toward multiculturalism. Catholic religion teachers hold a strategic position in guiding students to become inclusive, open-minded individuals who are capable of living harmoniously in a pluralistic society.